KEKUATAN GESER ANTARMUKA LATERIT PALANGKARAYA DAN GEOTEKSTIL BERDASARKAN UJI GESER LANGSUNG - Norseta Ajie Saputra (Lambung Mangkurat University Press, 2013)
Laterite soil is used to support the development of transportation infrastructure such as roads. The use of geotextile as soil reinforcement material is one of the geotechnical engineering practices. The use of geotextile material and lateritic soil for pavement reinforcement requires parameters from lateritic soil and its interaction with geotextile. Planning and implementation work in the field normally use the ratio interface friction angle soil and geotextile friction angle (  /  ), where   is value of interface friction angle between geotextile and laterite (  ) and  is value of angle of internal friction laterite (  ). The ratio (  /  ) was obtained from direct shear test method ASTM D 3080-70. The laterite soil was compacted using a test proctor at a maximum density condition or with a value of optimum water content. The laterite soil came from two locations in Central Kalimantan province distinguished by the closer proximity to the City of Palangka Raya. The geotextile was is Geo- reinforcement HRX 250 and HRX 300. The result showed the value of the ratio  /  for Palangka Raya laterite soil based on two samples of different geotextile types. For the woven geotextile reinforcement HRX 250 (fine), the value  /  was 0.81 to 0.90, and for the woven geotextile reinforcement HRX 300 (rather coarse), the value  /  was 0.75 to 0.77. The ratio  /  is not significantly influenced by the geotextile mass, strength and elongation values. It is the soil types and characteristics that actually influence this ratio